Chapter El licenciado Francisco de Rojas, enmendador barroco de manuscritos teatrales - Garcia-Reidy, Alejandro (Studi e saggi, 2021)
This paper focuses on the figure of the graduate Francisco de Rojas, a minor playwright from the first half of the seventeenth century who is better known for copying several theatrical manuscripts and, above all, for the presence of his handwriting in dozens of other manuscripts. The objectives of this paper are to contextualize his activity as a copyist, to systematize the nature of his interventions in the dialogues of the plays, and to point out the-often silent-influence that Rojas' amendments have had in several editions of early modern Spanish plays for over a century.